2021
DOI: 10.3390/jcm10163479
|View full text |Cite
|
Sign up to set email alerts
|

Female Gender Is Associated with Higher Susceptibility of Weight Induced Arterial Stiffening and Rise in Blood Pressure

Abstract: Arterial stiffness is an important predictor of cardiovascular events, independent of traditional risk factors. Stiffening of arteries, though an adaptive process to hemodynamic load, results in substantial increase in the pulsatile hemodynamic forces that detrimentally affects the microcirculation perfusing the vital organs such as the brain, heart and kidneys. Studies have proposed that arterial stiffness precedes and may contribute to the development of hypertension in individuals with obesity. Our study so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 49 publications
(55 reference statements)
1
13
1
Order By: Relevance
“…A major limitation of our study is that females were under-represented, only comprised about 27.5% of the total study population, and only 7% of them were in overweight or obese. However, the results are consistent with our findings previously published [ 25 ], showing that overweight and obese females are more susceptible to weight-related hypertension associated with faster degeneration of the elastic arteries. Furthermore, the current study was an observational study and did not examine the effect of a greater BMI on endpoint events.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…A major limitation of our study is that females were under-represented, only comprised about 27.5% of the total study population, and only 7% of them were in overweight or obese. However, the results are consistent with our findings previously published [ 25 ], showing that overweight and obese females are more susceptible to weight-related hypertension associated with faster degeneration of the elastic arteries. Furthermore, the current study was an observational study and did not examine the effect of a greater BMI on endpoint events.…”
Section: Discussionsupporting
confidence: 93%
“…Besides analyzing the whole cohort, we hypothesized that some features related to different class of BMI might be partly associated with sex, as we previously reported [ 25 ]; thus, we also grouped and further analyzed males and females separately.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings were consistent with a cross-sectional study ( 13 ) that also indicated that individuals with overweight/obesity, instead of those with normal weight, had significant associations between elevated baPWV levels and diabetes risk. Another study revealed that women had higher susceptibility of arterial stiffening in obesity which predispose to hypertension ( 31 ). However, there was evidence showing a lower degree of stiffness in large arteries of overweight-obese subjects compared to their normal-weight counterparts ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Gender differences have been reported for several conditions affecting arterial stiffness and/or the autonomic control of the heart: BP [ 6 , 22 ] and heart rate variability [ 23 ], walking speed [ 24 ], insulin resitance [ 25 ], and body weight and shape [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%